Bettina Mottura, Letizia Osti, and Giorgia Riboni (editors), Media and Politics. Discourses, Cultures, and Practices (Newcastle upon Tyne, Cambridge Scholars Publishing, 2017, 504 pp. ISBN 152-750-022-5) - Francesco Meledandri (Altre Modernità, 2020)
Bettina Mottura, Letizia Osti, and Giorgia Riboni (editors), Media and Politics. Discourses, Cultures, and Practices (Newcastle upon Tyne, Cambridge Scholars Publishing, 2017, 504 pp. ISBN 152-750-022-5)